Pose tracking with rate gyroscopes in alpine skiing - Yoshioka, S.; Fujita, Z.; Hay, D. C.; Ishige, Y. (Sports Engineering, 2018)
The motion capture of alpine skiing is technically challenging. Motion capture systems using inertial sensors such as gyroscopes and accelerometers have begun to be used in sport. The capture volume of the system can be large enough to cover the whole area of a particular sporting event, because sensors are affixed to the human body itself. The current study developed a method of tracking the pose of an alpine skier using gyroscopes for 3 min with a tracking error of 2° (RMSE). The technical significance of the presented method, which uses one common simple algorithm to improve measurement of pose, applies to many experimental conditions. The adoption of a high resolution (24 bit) analog-to-digital converter and high sampling rate (1 kHz) also contribute to the improvement of measurement time.